2017
DOI: 10.3390/ijgi6110358
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Determinants of Housing Prices in Beijing: An Enhanced Hedonic Regression with Open Access POI Data

Abstract: Abstract:The housing market in Chinese metropolises have become inflated significantly over the last decade. In addition to an economic upturn and housing policies that have potentially fueled the real estate bubble, factors that have contributed to the spatial heterogeneity of housing prices can be dictated by the amenity value in the proximity of communities, such as accessibility to business centers and transportation hubs. In the past, scholars have employed the hedonic pricing model to quantify the amenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 72 publications
3
54
1
2
Order By: Relevance
“…Yang [58] demonstrated that a shorter distance from residential developments to the city centre has a significant and positive impact on housing prices in Beijing. In contrast, Xiao et al [26] indicated that a shorter distance from houses to city sub-centres increases Beijing's real estate values. These two studies did not indicate whether the two distances impact Beijing's housing prices simultaneously.…”
Section: Impact Of Location Characteristics On Housing Pricesmentioning
confidence: 97%
See 3 more Smart Citations
“…Yang [58] demonstrated that a shorter distance from residential developments to the city centre has a significant and positive impact on housing prices in Beijing. In contrast, Xiao et al [26] indicated that a shorter distance from houses to city sub-centres increases Beijing's real estate values. These two studies did not indicate whether the two distances impact Beijing's housing prices simultaneously.…”
Section: Impact Of Location Characteristics On Housing Pricesmentioning
confidence: 97%
“…In addition, we added the number of bus stations and schools within 0.5 km and 1 km road distances into the model (0.5 km: BUS_5H, SUB_5H, and SCH_5H; 1 km: BUS_1T, SUB_1T, and SCH_1T). As indicated by the statistics in Table 1, the densities of bus stations, metro stations, and schools could have an impact on housing prices, since the concentration of amenities can have an impact on the housing prices of residential units [26]. Except for the traffic and educational aspects, several independent variables were used to measure and explain several natural or semi-natural amenities, including PARK_DIS, LAKE_DIS, LAKE_AREA, RIVER_DIS, and HGVI.…”
Section: Hedonic Pricing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, a project has been proposed to give a solution in underwater environments, providing an underwater location system [15] using beacons. Until now, all aforementioned applications and projects have made use of Bluetooth technology for POIs as a sensor dependent on other technologies, such as an Internet connection, to retrieve the information about the place, as shown in [16,17]. This is not the case of the proposal described in this work.…”
Section: State Of the Artmentioning
confidence: 57%